REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA PERANG DAGANG AMERIKA SERIKAT DAN CHINA - Yani Rahmawati; Hendra Gunawan (JOURNAL OF APPLIED MANAGERIAL ACCOUNTING, 2021)
This research is an event study which aims to analyze the reaction of the Indonesian capital market, especially on LQ45 shares before and after political events that occur abroad. The event that became the object of observation was the trade war that occurred between the United States and China by using 12 events related to trade wars starting from 2014 to 2019, using the abnormal return indicator. The sample in this study are companies that are in the LQ45 stock index. The data used is secondary data in the form of the company's daily closing price and the Composite Stock Price Index (CSPI). The statistical test used to test the research hypothesis is the paired t-test which was tested on 11 events, and there was 1 event using the Wilcoxon test. The results showed that the trade war between the United States and China did not result in a significant difference in abnormal returns on LQ45 stocks with the observed period. So it can be said that the Indonesian capital market did not react to the 12 events of the trade war between the United States and China.